Environmental Participation and Environmental Motivation - Benno Torgler; María A. García-Vali\~nas; Alison Macintyre (Center for Research in Economics, Management and the Arts (CREMA), 2009)
We explore whether environmental motivation affects environmental behavior by focusing on volunteering. The paper first introduces a theoretical model of volunteering in environmental organizations. In a next step, it tests the hypothesis working with a large micro data set covering 32 countries from both Western and Eastern Europe using several different proxies to measure environmental motivation. Our results indicate that environmental motivation has a strong impact on individuals' voluntary engagement in environmental organizations. A higher level of environmental motivation due to higher environmental moral standards may lead to a stronger voluntary involvement in environmental organizations.
Keywords: D11; H41; H26; H73; D64; 330; environmental participation; environmental motivation; environmental morale; pro-environmental attitudes; social capital